(untitled) (Annals of Medical Research, 2021)
Aim: To obtain data which could be of guidance in the selection of empirical antibiotic treatment through bacteria isolation from sputum and antibiotic sensitivity tests in patients hospitalised because of exacerbation of chronic obstructive pulmonary disease (COPD). Materials and Methods: Sputum samples were induced before antibiotherapy in patients hospitalised because of COPD exacerbation. In addition to routine tests and infection markers, sputum cultures and antibiotic resistance tests were applied. Results: The study included 101 patients. Production was determined in the sputum cultures of 28 (27.7%) patients. In the group with bacteria isolated in the sputum, there was determined to be a high number of exacerbations in the last year, partial oxygen pressure (PaO2) was low, and procalcitonin (PCT), the neutrophil ratio, white blood cell count (WBC) and the modified Medical Research Council Dyspnea Score (mMRC) were found to be higher than in the patients with negative sputum (p<0.05). The three leading bacteria produced in the positive culture group were Streptococcus pneumonia,Pseudomonas aeruginosa and Acinetobacter spp. Conclusion: S. pneumoniae, P.aeroginosa and Acinetobacter spp. are still the most common organisms which were isolated in acute exacerbation of COPD in our country population. Ceftriaxone is still considered a highly sensitive and effective antibiotic drug against these common micro-organisms in our society, besides that procalcitonin value is the most useful tracking parameter for these patients. Consequently, intermittent surveillance regarding improving of resistance pattern for these common pathogens against commonly prescribed drugs is necessary.